Erratum: Weighing the giants – V. Galaxy cluster scaling relations. Issue 3 (21st February 2017) - Mantz, Adam B.; Allen, Steven W.; Morris, R. Glenn; von der Linden, Anja; Applegate, Douglas E.; Kelly, Patrick L.; Burke, David L.; Donovan, David; Ebeling, Harald
Abstract :